Association between body mass index and happiness in Africa, the Russian Commonwealth, Europe, Latin America, and South Asia. (23rd April 2019) - Yuen, Thomas Wai-Kee; Chu, Winnie Wan-Ling
The issues of overweight and obesity are getting worse. In fact, overweight and obesity are killing more people than underweight in many counties. This paper examines the association between body mass index (BMI) and happiness in different regions including Africa, the Russian Commonwealth, Europe, Latin America, and South Asia using parallel panel data from 88 countries. This paper estimates random effects panel data models with instrumental variables using generalised method of moments (GMM) approach. The empirical results show that lifestyles vary between regions, thus the contribution of happiness to the prevalence of overweight and obesity varies across different regions. Life happiness does not have much effect on overweight and obesity in Africa, Latin America, or the Russian Commonwealth. However, life happiness contributes positively to overweight but not to obesity in South Asia. In South Asia, being a little bit fat or overweight is a sign of happiness, but being obese is a sign of unhealthy.